Both platelet- and endothelial cell–derived ERp5 support thrombus formation in a laser-induced mouse model of thrombosis - Passam, Freda H. (Blood, 2015)
Protein disulfide isomerase (PDI) and endoplasmic reticulum protein 57 (ERp57) are emerging as important regulators of thrombus formation. Another thiol isomerase, endoplasmic reticulum protein 5 (ERp5), is involved in platelet activation. We show here the involvement of ERp5 in thrombus formation using the mouse laser-injury model of thrombosis and a specific antibody raised against recombinant ERp5. Anti-ERp5 antibody inhibited ERp5-dependent platelet and endothelial cell disulfide reductase activity in vitro. ERp5 release at the thrombus site was detected after infusion of Alexa Fluor 488–labeled anti-ERp5 antibody at 0.05 μg/g body weight, a dose that does not inhibit thrombus formation. Anti-ERp5 at 3 μg/g body weight inhibited laser-induced thrombus formation in vivo by causing a 70% decrease in the deposition of platelets and a 62% decrease in fibrin accumulation compared to infusion of control antibody (P < .01). ERp5 binds to β3 integrin with an equilibrium dissociation constant (K(D)) of 21 µM, measured by surface plasmon resonance. The cysteine residues in the ERp5 active sites are not required for binding to β3 integrin. These results provide evidence for a novel role of ERp5 in thrombus formation, a function that may be mediated through its association with αIIbβ3.